Proposed new interior design scheme for Lomography Gallery Store at No.1 & No.2 Jalan Telawi 3 , Bandar Baru Bangsar , 59100 Kuala Lumpur for Eight Layers Sdn. Bhd. / Siti Amirah Mohd Reduan - Mohd Reduan, Siti Amirah (Faculty of Architecture, Planning and Surveying, 2012)
The Project Report is compulsory for every final semester student of Department of Interior Architecture. The report would be a detailed explanation of their final project for Diploma of Interior Design course. The report consists of introduction to the project, background on the client, detail on proposed site, studies on case study, followed by the design process that involves. The early process of the project involves a lot of researching and seeking information on especially on client and site. Then the next phase involves study of case study, where the students need to understand and deeply research on the case study. At this stage lot of interviews and observation are involve as to understand more of the nature of business and history of the case study. The final stage of the project, more critical thinking are needed as the student need to take all of the information that were obtained and figure out solutions for design issues by using as much from it.